Emergent Pulmonary Embolectomy and Advanced Glioblastoma Multiforme. (28th November 2010) - Firstenberg, Michael S.; Blais, Danielle; Abel, Erik; Newton, Herbert B.; Crestanello, Juan
Abstract : Pulmonary emboli are frequent causes of morbidity and mortality in patients with brain tumors. Treatment options are limited in these complex patients. We report a case of successful acute pulmonary embolectomy in a patient with an advanced brain cancer.